Studies on the Selectivity of Porous Methacrylate Polymers - B. Gawdzik; M. Maciejewska (Adsorption Science & Technology)
Four types of porous methacrylate polymers were synthesized as stationary phases for gas chromatography. The influence of the chemical structure of the monomers used in the synthesis on the selectivities of the resulting polymers was studied. Two procedures were applied to determine the selectivities of the copolymers: the selectivity triangle and the general selectivity. Porapak Q, the least polar commercially available porous polymer, was used as a reference phase.